2013
DOI: 10.1016/j.jacceco.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Individual investors and financial disclosure

Abstract: Using detailed data of individual investors, this dissertation investigates whether and how individuals use financial disclosure and analysts' signals. Chapter 1 shows that, on average, individuals invest more in firms with readable, concise, and transparent financial disclosures.The results indicate that these relations are less pronounced for overconfident investors, and that individual investors appear to place a greater weighting on such financial disclosure attributes relative to institutional investors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
278
1
30

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(343 citation statements)
references
References 54 publications
6
278
1
30
Order By: Relevance
“…The study by Lawrence (2013) revealed that higher quality financial disclosures by firms encourage individuals to risk and invest more. The importance of information access has also been confirmed by examining insiders who have access to relevant information about the firm's performance, in a study by Van Geyt et al (2013), shows that insiders benefit from inside information during financial crisis trading, and which resulted in higher profits.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Lawrence (2013) revealed that higher quality financial disclosures by firms encourage individuals to risk and invest more. The importance of information access has also been confirmed by examining insiders who have access to relevant information about the firm's performance, in a study by Van Geyt et al (2013), shows that insiders benefit from inside information during financial crisis trading, and which resulted in higher profits.…”
Section: Discussionmentioning
confidence: 99%
“…Miller (2010) finds that retail investors trade fewer shares in firms with less readable and larger annual reports, while Lawrence (2013) finds that small investors invest more in firms with more readable and shorter annual reports. Analysts are also impacted by the readability of annual reports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, Chiyachantana, Jiang, Taechapiroontong and Wood (2004) find that retail trading increased relative to institutional trading around earnings announcements after Regulation Fair Disclosure was introduced in the US, consistent with retail investors abstaining from trading when they fear institutional investors have better information. Similarly, Lawrence (2013) provides evidence based on brokerage data that retail investors invest more and obtain higher returns in firms with more detailed and more readable annual reports and that these associations are less pronounced for investors with a professional background.…”
Section: Experimental Evidence Indicates That Retail Investors Tend Tmentioning
confidence: 99%